Relative efficacy and safety of non-Vitamin K oral anticoagulants for non-valvular atrial fibrillation: Network meta-analysis comparing apixaban, dabigatran, rivaroxaban and edoxaban in three patient subgroups. (1st February 2016) - Lip, Gregory Y.H.; Mitchell, Stephen A.; Liu, Xianchen; Liu, Larry Z.; Phatak, Hemant; Kachroo, Sumesh; Batson, Sarah
Abstract: Background: Stroke is the most serious clinical consequence of atrial fibrillation, which is the most common cardiac arrhythmia. Non-vitamin K antagonist oral anticoagulants (NOACs) have emerged as efficacious, safe and convenient stroke prevention agents. This updated network meta-analysis focused on the relative efficacy and safety of apixaban compared with dabigatran, rivaroxaban and edoxaban for stroke prevention in (i) patients with CHADS2 score ≥ 2, (ii) secondary stroke prevention, and (iii) patients with high quality anticoagulation control with warfarin. Methods and results: A fixed-effects network meta-analysis was conducted, including data from four Phase III randomised controlled trials (> 70, 000 patients with non-valvular atrial fibrillation). The results of the base-case analysis comparing NOACs with warfarin were broadly in line with the results from the individual trials. Results from the three subgroup analyses were broadly similar to the base case results. For example in patients with CHADS2 score ≥ 2, apixaban, high-dose dabigatran, rivaroxaban, and high-dose edoxaban had significantly lower hazards of stroke/systemic embolism compared with low-dose edoxaban. Apixaban and low-dose edoxaban were associated with significantly lower hazards of major bleeding compared with rivaroxaban and dabigatran 150 mg. However, several treatment comparisons that were significant in the base-case analysis were not significant in the patient subgroups, due to the reduced sample size of the subgroups compared with the overall population. Conclusions: Among the NOACs, apixaban offered the most favourable efficacy and safety profile in the overall patient population as well as in the three subgroups investigated.